ANALISIS PERUBAHAN TUTUPAN VEGETASI BERDASARKAN NILAI NDVI DAN FAKTOR BIOFISIK LAHAN DI CAGAR ALAM DOLOK SIBUAL-BUALI - Ardiansyah Putra; Anita Zaitunah; Muhdi Muhdi (Peronema Forestry Science Journal, 2016)
The absence of information about the level of change in vegetation index (NDVI) of forest land in the Nature Reserve Dolok Sibual-Buali is unclear. The decrease of NDVI would be related to forest damage. Forest damage will impact on the decrease of forest functions, especially its function as regulator of water management, flood prevention, erosion and carbon sequestration. This research was conducted in Nature Reserve Dolok Sibual-buali in May-September 2009 using Geographic Information System (GIS), Remote Sensing (RS) and Global Positioning System (GPS), which are three very useful spatial technology. Spatial analysis was done by overlaying several spatial data (parameters determining forest damage vulnerability level) to produce a new mapping units (land units) which will be used as the unit of analysis. The results showed regional nature reserve area Dolok Sibual-Buali is well preserved with class area from 0.4 to 0.8 (tropical rain forest) amounted to 4049.71 hectares, an increase of 32.15% vegetation cover to the class from 0.4 to 0.8 (tropical rain forest) in the nature reserve area Dolok Sibual-buali. Based on the analysis, nature reserve area Dolok Sibual-buali well preserved becausedof biophysical conditions taht forest cover which is at a high altitude with a moderate to steep slopes and quite far from the road and also does not have a big river. Causing difficulty of access into the area and also the absense of conveyace of natural wood. Keywords: GIS, RS, NDVI, Vegetation Coverage Change, overlays, Dolok Sibual-buali Nature Reserve